A influência dos jogos didáticos no processo de ensino e aprendizagem: uma abordagem a partir da neurociência - (:unkn) unknown (Universidade Federal do Pampa, 2019)
Interest in the theme of this work was due to the importance of showing that the teaching process does not have to be painful and regulating in school, and that students can learn without having to memorize and write repeatedly to understand the content, but that the school is a privileged space for the construction of knowledge in a relaxed way. The perception of teaching and learning comes over time trying to adapt to the concept of working the playful (educational games) in the classroom in order to contribute to education, understanding that this work contributes to the conception of multiple intelligences where it encompasses the possibilities of spatial, logical, verbal, arts, kinesthetic-body work, among others. The didactic games promote the intellectual development considering that to overcome the challenges of this activity the player needs to understand how the different elements of the game relate, to elaborate strategies, to make decisions to process information and to solve problems, besides to generate emotions that can function as modulators of our memories that refer to a fundamental component of learning, so neuroscience comes together in this possibility of practice in order to scientifically corroborate the importance of working other forms of teaching that can help strengthen brain plasticity. where the stimulus process is very important, thus making learning more meaningful and permanent for the student. We can observe that neuroscience in partnership with other disciplines may present a new aspect in its interventions the methodology of teaching and arresting when finding in neuroeducation a support base to improve learning. In this sense, this project aims to investigate the Brazilian academic production related to the influence of playful games in the educational process, from a neuroscientific approach focusing on elementary school. It is expected to contribute to the elucidation about the "state of the art" of academic production related to the educational influence of playful games with neuroscientific approach.
The influence of didactic games in the teaching and learning process: an approach based on neuroscience
Keywords: Educação; Jogos; Neurociência; Education; Games; Neuroscience; Educação e neurociência; Education and neuroscience; CNPQ::CIENCIAS DA SAUDE